An Exploratory Study of Low-Income Minority Students Online Learning Experience - Eugene Kwasi Gyekye; Julie Learned (Online Learning)
This study draws on the theory of Cumulative Disadvantage and Advantage (CDA) (Merton,1968; Dannefer, 2003; Northrop, 2017) to explore the online learning experiences of Low-income minority students in middle school.  I examine inequitable access to technology and the underdevelopment of technological skills by minority students. The study sought to answer How intermediate school students from low-income minority communities describe their online learning experiences? In a qualitative school-year-long survey, I interviewed two middle school students across classes in an urban middle school and interviewed two teachers who teach these students. Using 300 hours of observations, analysis of interview data showed that minoritized students experience comfort and discomfort when learning online. Comforting teacher behaviors mitigate these learner discomforts. By documenting online learning experiences of Low-income minority students, findings have implications for educational equity and promoting socially just teaching.